2020
DOI: 10.1016/j.redox.2019.101379
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress regulates cystathionine γ lyase expression to preserve endothelial redox balance and reduce membrane lipid peroxidation

Abstract: Cystathionine γ lyase (CSE) is the major source of hydrogen sulfide-derived species (H2Sn) in endothelial cells and plays an important role in protecting against atherosclerosis. Here we investigated the molecular mechanisms underlying the regulation of CSE expression in endothelial cells by fluid shear stress/flow. Fluid shear stress decreased CSE expression in human and murine endothelial cells and was negatively correlated with the transcription factor Krüppel-like factor (KLF) 2. CSE was identified as a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 56 publications
(82 reference statements)
2
29
0
Order By: Relevance
“…Bibli et al ( 30 ) found that treatment with SG1002 of human umbilical vein endothelial cells induced protein S-sulfhydration and concomitantly protected membrane lipids from peroxidation; these in vitro findings are consistent with the significant increases in H 2 S and/or SS levels of blood and tissues attained when SG1002 is orally administered to mice ( 134 ), swine ( 210 ), and humans ( Fig. 4 ) ( 196 ).…”
Section: Sg1002: An Overviewmentioning
confidence: 58%
See 1 more Smart Citation
“…Bibli et al ( 30 ) found that treatment with SG1002 of human umbilical vein endothelial cells induced protein S-sulfhydration and concomitantly protected membrane lipids from peroxidation; these in vitro findings are consistent with the significant increases in H 2 S and/or SS levels of blood and tissues attained when SG1002 is orally administered to mice ( 134 ), swine ( 210 ), and humans ( Fig. 4 ) ( 196 ).…”
Section: Sg1002: An Overviewmentioning
confidence: 58%
“…Participants Country: Mexico (State University of Nuevo León, UANL, Monterrey) Infertile men recruited from UANL's Reproductive Biology Clinic at the University Hospital. Mean age: 34.23 (range[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. n = 44 men completed the study.…”
mentioning
confidence: 99%
“…Unlike apoptosis, ferroptosis is characterized by excess reactive oxygen species (ROS) and intracellular iron 5 . Superabundant ROS induces peroxidation and disintegration of lipid membrane and cell death 6 . Regulation of ferroptosis mainly depends on neutral reaction between reduced glutathione (GSH) and ROS 7 .…”
Section: Introductionmentioning
confidence: 99%
“…While laminar flow was initially demonstrated to enhance the expression of CSE and 3-MST in ECs [ 47 , 48 ], recent data are more complex. In particular, laminar flow (high shear stress) has been demonstrated to inhibit CSE expression via KLF2 regulated miRNA-27b [ 49 ], while turbulent flow (low shear stress) seems to upregulate CSE [ 50 , 51 ]. In rat aortic ECs, calcium-sensing receptors increase CSE expression in a phospho-calmodulin kinases II-dependent manner to inhibit platelet activation [ 52 ].…”
Section: Biochemistry Of H 2 S Productionmentioning
confidence: 99%
“…Most persulfidation reactions lead to target inhibition as phosphatase and tensin homolog (PTEN) [ 65 ], except for MEK1 activity, which in HUVEC leads to increased activity with DNA damage repair and senescence impairment [ 66 ]. Recently, Prx6 has been identified as a further target of sulfhydration on Cys47, which controls its decamerization and peroxidase activity [ 49 ], while the “S-sulphydrome” was identified among the many target proteins, and β3 integrin was identified as the key element of endothelial mechanotransduction [ 67 ].…”
Section: Molecular Signaling Activated By H 2 Smentioning
confidence: 99%